European Union standards for Ukrainian inland waterways: Directive № 87/540/EEC (Part II) - Sergiy Kuznetsov; Valeriya Slatvinska (Lex Portus, 2018)
The article is devoted to the study of the provisions of the current Ukrainian legislation and the provisions of Council Directive 87/540/EEC with a view to determining the conditions for its implementation and realization of its provisions in Ukraine. The place of the Directive in the system of Ukrainian legislation has been determined. Furthermore, it was proved that the Directive does not deal directly with drivers, as carriers, but with transport operators. Besides, the authors conducted a comparative legal study of the provisions of the Directive 87/540/EEC and the text of the official Ukrainian translation of the Directive. The authors noted that the occupation of carrier of goods by waterway in national and international transport is sphere of activity by Directive. Additionally, the effect of the norms of the Directive in space and in a circle of persons was studied. So the scope of the Directive for the type of activity is an entrepreneurial activity, which is not related to the direct transportation of goods, but to the availability of professional knowledge and appropriate qualifications in management and / or operation - the organization of transport operations, in particular those that are directly related to the transport of goods and the monitoring of their implementation. Also the authors mentioned that Ukrainian legislator uses the notion of “inland waterway”, without even defining it. Finally, the conceptual-terminological apparatus, namely, the terms “occupation”, “transportation”, “goods”, “waterway vessel”, “carrier”, “actual carrier”, “performing carrier”, “shipping company”, “inland waterways”, national (coastal) and international water transport are analyzed. Moreover, the concepts have been investigated by comparing their meanings in the Directive, the Ukrainian legislation and legal dictionaries.